SOMATIC ASPECTS OF SPORTS CHAMPIONSHIP IN TAEKWON-DO ITF - Wladyslaw Jagiello; Zh.L. Kozina; Marina Jagiello (Physical Education of Students, 2015)
The purpose of the study is to answer a basic question: which somatic characteristics of taekwon-do ITF athletes correlate the most with their sports level and experience training. Material: Representatives of the Polish taekwon-do ITF national team (n=21) took part in the study. The subjects’ age was in the range of 18.51-32.22 years (24.5±4.1), and their training experience 8.4-22.4 years (13.6±3,4). Results: Measurements of 20 basic somatic characteristics were taken. It was determined that correlations with the sports level and training experience were non-homogeneous and diverse due to the represented weight category. Conclusions: correlations of somatic indices with sports level and training experience among Polish representatives in taekwon-do are heterogeneous and largely dependent on weight category.